691 Distribution of wall motion abnormalities in young patients presenting with acute coronary syndrome. (8th December 2021) - De Santis, Giulia; Pistelli, Lorenzo; Franzino, Marco; Nicolo, Claudio; Parisi, Francesca; Cusma, Maurizio; Trio, Olimpia; Manganaro, Roberta; Zito, Concetta; Carerj, Scipione; Di Bella, Gianluca; Micari, Antonio; et al.
Abstract: Aims: Distribution of wall motion abnormalities (WMA) in young patients presenting with acute coronary syndrome (ACS) is not well described. Methods and results: We included 91 consecutive young patients (≤45 years at presentation) with ACS with obstructive or without obstructive coronary artery disease referred from October 2013 until March 2021 to our clinic. Wall motion abnormalities, wall motion score index (WMSI) and left ventricle ejection fraction (LVEF) were evaluated. A wall motion abnormality in at least one segment was present in 78.7% of patients. Mean LVEF was 50.9 ± 8.8% and mean WMSI was 1.38 ± 0.37%. Akinesia of at least one segment was present in 49.4%, dyskinesia and aneurysm were rare (1.1%, respectively). Ventricular thrombus was observed in 4.7%. Distribution of wall motion abnormalities is presented in Figure A. Most frequently WMA affected the apex and the basal inferior wall. The severity of WMA for each segment is presented in Figure B. The mean highest severity of WMA affected the apex, and the inferior and infero-septal wall. In the subgroup of patients presenting without obstructive coronary artery disease, WMA were less prevalent (37.5%), LVEF was higher (57.1% vs. 50.4% P  = 0.032), and WMSI was lower (1.16% vs. 1.40% P  = 0.07), but similarly affected with higher frequency the apex area. Conclusions: In conclusion, WMA are frequent in young patients presenting with ACS, mostly affecting the apex. More severe abnormalities of wall kinesis affect the apex and the inferior and infero-septal wall.